Understanding Correspondent Banking Trends : A Monitoring Framework - Jan Grolleman, Dirk.; Jutrsa, David (Washington, D.C. : International Monetary Fund, 2017)
The withdrawal of correspondent banking relationships (CBRs) remains a concern for the international community because, in affected jurisdictions, the decline could have potential adverse consequences on international trade, growth, financial inclusion, and the stability and integrity of the financial system. Building on existing initiatives and IMF technical assistance, this paper discusses a framework that can be readily used by central banks and supervisory authorities to effectively monitor the developments of CBRs in their jurisdiction. The working paper explains the monitoring framework and includes the necessary reporting templates and an analytical tool for the collection of data and analysis of CBRs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet